Multi-agent systems modeling integrating geographic information systems and remote sensing tools for participatory resource management : prototype for Loon in Bohol, Philippines - Campo, Paolo C. (2003)
This research tried to develop a methodology for building a Multi-Agents Systems simulation model integrating Geographic Information Systems and Remote Sensing for participatory natural resource management. The methodology, based on a modified conceptual framework of Pahl-Wostl (2002), involved the use of MAS, GIS, RS techniques for data collection and processing, MAS conceptual and computer modelling, and MAS model verification and validation using a participatory approach. By using MAS, GIS and RS technologies in its construction and analysis, the MAS model is hoped to be used as a learning tool for the participants of an NRM situation. Moreover, the MAS model and its results are anticipated to used as take-off points for discussion and negotiations in participatory NRM. One of the main outputs of this research was a working MAS simulation model for the case of the Municipality of Loon, Bohol, Philippines. To be be able to build the simulation model, called the Bohol model, a two-part fieldwork in the study area was conducted by a research team, which included this researcher, to familiarize themselves with the people's perception of their current NRM situation and its problems. Also the fieldwork allowed the researchers to gather spatial information on the study area, and details about activities of the locals with regards to the use of their natural resources. All these information were processed and integrated in the MAS simulation model. The Bohol model was only a skeleton for possible future MAS models for NRM; as of now, it does not mimic the real NRM situation. A lot of assumptions have been made such as model for fish reproduction and forest growth, to make the model run. However, based on the simulations conducted, it demonstrated how individual actions of agents collectively affected its environment. Scenarios were developed based on the initial findings of the fieldwork, and these scenarios were tested inside the Bohol model. From the results of the simulation of the scenarios, the model was able to demonstrate the effects of changing the parameters of the model, specifically parameters related to agent behavior. The use of spatially-explicit models, such as GIS and RS models, as a learning tool offer the participants of an NRM situation a new way to see their natural resources and environment by means of digital maps. It's a way for them to see their environment from "outside the box." Through its use, the MAS models may enhance the learning experience by means of running simulation. The participants of an NRM situation may see the MAS model simulation as a "movie" about themselves and their possible future with them being the actors of this movie. Adding GIS and RS techniques to analyze the results of the simulation may add to this experience by offering ways to visualize the results of the actor's actions by means of change-detection maps, charts and cross-tabulations.